The perspective of students and graduates on the architecture education in the Malaysian context/ Alice Sabrina Ismail and Suhaila Mohd Siraj - Ismail, Alice Sabrina; Mohd Siraj, Suhaila (Universiti Teknologi MARA, Perak, 2024)
Architectural education is essential to produce the profession of the architect responsible for creating a quality environment in the 21st Century. Therefore, architecture education should be holistic, addressing the needs of architecture graduates with six attributes: ethics and spirituality, leadership skills, national identity, language skills, thinking skills, and knowledge to meet the needs of the industry and the current market in parallel with the requirements of the national policy. However, not many past studies have been provided on architectural education in Malaysia, from the students' perspectives to hold on to the profession of an architect. Most past studies focus only on pedagogical methods of learning and evaluation of architectural studios, the application of technology in architectural education, the element of entrepreneurship in architectural education, and the importance of sustainability values in the architectural curriculum. Therefore, this study aims to identify architecture students' perspectives in private and public universities and outline proposals to improve the current architecture education curriculum to produce better architecture graduates. The methodology used involves a combination of quantitative research. The scope of study is focused only on architectural programmes subject to LAM (Malaysia Architect Council) Part I and II recognition. The findings underline the need for quality teaching and learning, emphasizing generic skills to produce graduates with high marketability values in the 21st Century.